A correlational study of the relationship between users acceptance and satisfaction towards behavioural intention - Mohd-Bashri, Nur Fathiah; Mat Yamin, Fadhilah (Discovery Publication, 2015)
The popularity of Facebook as social interaction tool among people worldwide cannot be denied. In Malaysia, Facebook become the most popular Social Networking Site (SNS) especially among the adoles- cents and young adults’ users in the age range of 18-35 years old.Thus, the purpose of this pilot study is to investigate the relationship between users’ acceptance and satisfaction factors towards behavioural intention among the adolescents and youth users in using Facebook as social interaction tool. The reliability of measures used in this study is acceptable because the Cronbach’s Alpha value for the variables and dimensions in this study is more than 0.7. Meanwhile all the hypotheses in this study are supported and in the line with the previous studies.